Availability Optimization of a Dragline Subsystem using Bayesian Network - Jana D.; Kumar D.; Gupta S.; Gupta K.K. (My University, 2025)
The dragline is the mainstay in surface mining and plays a crucial role in the economic operation of large open cast mining projects. Draglines are very complex in design and consist of hundreds of components. Ensuring the high availability of a dragline is much necessary to achieve the target production. This paper aims to optimize the availability of a critical subsystem of a dragline through retrospective analysis of past operational data. The rope segment, one of the most critical subsystems of a dragline, has been considered for the study. The availability of the rope segment has been analyzed using Bayesian network (BN) model. It has been observed that the availability of rope segment is 94.8% and drag rope is the most critical component of rope segment. The availability of the components has been optimized using a target value approach which results in a 2.46% increased availability of the rope segment. © The Institution of Engineers (India) 2023.